Effect of coupling on the performance a periodic leaky wave patch antenna - G.L, Charmolavy; Moukengue , Nkouka; Mafouna Kiminou , Barol (International Journal of Engineering and Technology, 2023)
This article demonstrates the effect of coupling between two metal strips and the substrate width of a periodic leaky wave patch antenna operating at 80 GHz. Increasing the width of the substrate and the distance between the metal patches results in directional radiation and a good reflection coefficient in the 72-86 GHz band.